Laku Ngenger sebagai Ide Penciptaan Film Fiksi - Rahmawati, Dewi; Handriyotopo, Handriyotopo (JPKS (Jurnal Pendidikan dan Kajian Seni), 2025)
Human development is a process aimed at expanding the range of choices available to individuals. However, in reality, people sometimes find themselves unable to choose, or even lacking any options at all. The low Human Development Index (HDI) in Brebes Regency, coupled with the low purchasing power of its residents, ultimately affects the average length of schooling for children in the area. Dropping out or not continuing to the next level of education becomes a common choice. Another alternative is to engage in ngenger living with and learning from someone more capable in various aspects to ease the economic burden at home while also fostering personal growth. This tradition of ngenger inspired the creation of a short fictional film using a linear plot structure. The film seeks to revive the values embedded in ngenger, which serves as a form of informal education. Ngenger teaches that everything in life happens through a process of cause and effect and does not occur suddenly. Nothing can be achieved instantly; it requires effort, struggle, and sacrifice.